2022
DOI: 10.3390/mi13091493
|View full text |Cite
|
Sign up to set email alerts
|

Laser Polishing Die Steel Assisted by Steady Magnetic Field

Abstract: To improve the surface roughness of SKD61 die steel and reduce the secondary overflow of the molten pool, a steady magnetic field-assisted laser polishing method is proposed to study the effect of steady magnetic field on the surface morphology and melt pool flow behavior of SKD61 die steel. Firstly, a low-energy pulsed laser is used for the removal of impurities from the material surface; then, the CW laser, assisted by steady magnetic field, is used to polish the rough surface of SKD61 die steel to reduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The traditional computational fluid dynamics method was used to solve the problem in this simulation. The heat transfer equation for a material surface governed by Fourier’s law is described as follows [ 30 ]: where is the density, is the temperature, is the time, is the velocity of molten pool flow, is the thermal conductivity, is the laser heat source, and is the modified heat capacity, which is defined as [ 31 , 32 ]: where is the specific capacity of solid materials, is the latent heat of melting, and is the liquid fraction, which can be described as [ 32 ]: where (1877 K) and (1900 K) are the solid and liquid temperatures of Ti6Al4V, respectively.…”
Section: Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The traditional computational fluid dynamics method was used to solve the problem in this simulation. The heat transfer equation for a material surface governed by Fourier’s law is described as follows [ 30 ]: where is the density, is the temperature, is the time, is the velocity of molten pool flow, is the thermal conductivity, is the laser heat source, and is the modified heat capacity, which is defined as [ 31 , 32 ]: where is the specific capacity of solid materials, is the latent heat of melting, and is the liquid fraction, which can be described as [ 32 ]: where (1877 K) and (1900 K) are the solid and liquid temperatures of Ti6Al4V, respectively.…”
Section: Numerical Modelmentioning
confidence: 99%
“… where can be written in COMSOL weak form format, and a detailed implementation is covered in ref. [ 30 ]. Our integral is equal to zero.…”
Section: Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a large number of scholars at home and abroad have conducted experimental studies on the laser polishing of different materials, including metals and glass [ 5 , 6 , 7 , 8 , 9 ]. However, due to the high melting point and the low creep rate of the ceramic materials themselves, there are fewer reports on the use of laser polishing in ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wang et al established a mathematical model of the regulation of the electromagnetic complex field on the gradient of the particle distribution enhanced by laser melting and injection and analyzed the influence of the electromagnetic complex field parameters on the flow field, temperature field, and particle distribution inside the melt pool [23]. To improve the rough surface of SKD61 die steel, and reduce the secondary overflow of the molten pool, Zhou et al adopted a steady magnetic-field-assisted laserpolishing method to study the effect of a steady magnetic field on surface morphology and melt pool flow behavior [24]. The study revealed that the steady magnetic field can inhibit the secondary overflow of the molten pool to slightly improve SKD61 surface roughness by reducing the velocity of the molten pool.…”
Section: Introductionmentioning
confidence: 99%